2015
DOI: 10.1111/1750-3841.13160
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Caffeic acid Phenethyl Ester and 4‐Vinylcatechol in Stripped Soybean Oil

Abstract: Caffeic acid was used to synthesize 4-vinylcatechol (4-VC) by thermal decarboxylation and to prepare caffeic acid phenethyl ester (CAPE) by esterification reaction. The identities of synthesized products were confirmed by (1)H NMR. Antioxidative activities of 4-VC and CAPE were compared with α-tocopherol and BHT in stripped soybean oil at 60 °C under the dark. To evaluate the degrees of oxidation at different concentrations and combinations, peroxide value (PV) and (1)H NMR were performed. From the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previous studies have confirmed that CAPE has active biological antioxidant and anti-fibrosis properties[ 5 , 6 , 19 , 20 ]. Considering the fact that HSC proliferation and activation are key during liver fibrosis[ 21 - 23 ], it is interesting to know whether CAPE treatment can influence HSC proliferation and activation.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have confirmed that CAPE has active biological antioxidant and anti-fibrosis properties[ 5 , 6 , 19 , 20 ]. Considering the fact that HSC proliferation and activation are key during liver fibrosis[ 21 - 23 ], it is interesting to know whether CAPE treatment can influence HSC proliferation and activation.…”
Section: Discussionmentioning
confidence: 88%
“…Para cada columna las letras (a-e) indican diferencias significativas (p < 0.05) según la prueba de rango múltiple de Duncan. et al, 2019;Jia et al, 2015Jia et al, , 2016. For conjugated dienes and aldehydes, the signal intensity was highest in the control and lowest in the sample with catechin added.…”
Section: )mentioning
confidence: 99%
“…CAPE was prepared by the chemical esterification reaction of CA and phenethyl alcohol using the method described in previous studies 5,8,9 . In short, CA 54 mg , phenethyl alcohol 180 mg , and 1.2 mL of THF were mixed in the test tube, and 108 mg of dicyclohexylcarbodiimide as a catalyst was added to conduct the esterification reaction for 8 h at room temperature.…”
Section: Synthesis Of Capementioning
confidence: 99%
“…Similarly, CAPE showed higher LnA/PA than CA, α-TO and AP, and CON p 0.05 at 32 h oxidation. Such antioxidative capacity is attributed to the structural characteristics of CAFE, which has an ortho-dihydroxyl group within its catechol ring, inhibiting oxidation as a hydrogen donor 9,35 .…”
Section: Change Of Fatty Acid Compositionmentioning
confidence: 99%